Three new diterpenoids from Croton laui Merr. et Metc. Issue 9 (3rd May 2017) - Yang, Li; Wu, Zhong-Nan; Zhang, Yu-Bo; Chen, Neng-Hua; Zhuang, Ling; Li, Yao-Lan; Wang, Guo-Cai
Abstract: Three new diterpenoids, including one labdane diterpenoid (1 ) and two cembrane diterpenoids (2 –3 ), were isolated from the aerial parts of Croton laui, along with four known analogues (4 –7 ). Their structures were elucidated by spectroscopic analysis and comparison with literature data. All compounds were evaluated for their cytotoxicity against two tumour cell lines. Abstract :